2007
DOI: 10.1111/j.1365-2966.2007.12312.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic galaxy alignments from the 2SLAQ and SDSS surveys: luminosity and redshift scalings and implications for weak lensing surveys

Abstract: Correlations between intrinsic shear and the density field on large scales, a potentially important contaminant for cosmic shear surveys, have been robustly detected at low redshifts with bright galaxies in Sloan Digital Sky Survey (SDSS) data. Here we present a more detailed characterization of this effect, which can cause anticorrelations between gravitational lensing shear and intrinsic ellipticity (GI correlations). This measurement uses 36 278 luminous red galaxies (LRGs) from the SDSS spectroscopic sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
533
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 263 publications
(572 citation statements)
references
References 117 publications
33
533
0
6
Order By: Relevance
“…However, one should be cautious about this argument for several reasons, most importantly because there has not yet been any quantitative observational confirmation of the scale and configuration dependence predicted by the quadratic model, and additionally because perturbation theory arguments show that the nonlinear evolution of the tidal field can generate a linear type alignment (Hui and Zhang, 2008). What is clear from observations is that the alignments of late-type galaxies on large scales, at least as measured by w ge (r p ), are consistent with zero and are certainly much less than for LRGs (Hirata et al, 2007;Mandelbaum et al, 2011).…”
Section: Intrinsic Alignments*mentioning
confidence: 58%
See 3 more Smart Citations
“…However, one should be cautious about this argument for several reasons, most importantly because there has not yet been any quantitative observational confirmation of the scale and configuration dependence predicted by the quadratic model, and additionally because perturbation theory arguments show that the nonlinear evolution of the tidal field can generate a linear type alignment (Hui and Zhang, 2008). What is clear from observations is that the alignments of late-type galaxies on large scales, at least as measured by w ge (r p ), are consistent with zero and are certainly much less than for LRGs (Hirata et al, 2007;Mandelbaum et al, 2011).…”
Section: Intrinsic Alignments*mentioning
confidence: 58%
“…Note that they predict only E-mode intrinsic alignments, because the alignments are linearly sourced by a scalar field. 58 Observations of LRGs in the SDSS have shown that the galaxy-ellipticity correlation 59 w ge (r p ) has the same power-law slope as the galaxy correlation function w g (r p ) ∝ r −0.7 (Mandelbaum et al, 2006;Hirata et al, 2007), with an amplitude that increases rapidly with LRG luminosity. This is a quantitative success of the linear model.…”
Section: Intrinsic Alignments*mentioning
confidence: 99%
See 2 more Smart Citations
“…However, 72 Natarajan the most exciting results on the masses, density profiles and the galaxy-mass correlation function at the present time are from the SDSS (Sloan Digital Sky Survey). Mandelbaum and collaborators (Mandelbaum et al 2006;Hirata et al 2007) find that mass traces light on these large scales as M/L ∼ L 0.5 ; the mass of a typical dark matter (DM) halo that hosts an early-type L * galaxy is 1.5×10 12 h −1 M ; more massive DM haloes host brighter galaxies and that the masses of haloes that host late-types are a factor of 2-4 lower. Fitting parametric models they find that both NFW and Einasto profiles offer good fits over the range 0.2 r v ir < r 1 h −1 Mpc; and the inferred concentration parameter c v ir for NFW profiles is consistent with expectations of a power-law distribution with halo mass from cosmological simulations.…”
Section: Galaxy-galaxy Lensing Constraints On Field Galaxiesmentioning
confidence: 99%